(untitled) (AYUSHDHARA, 2024)
Objectives: Glenohumeral is a ball and socket type of synovial joint which permits a wide range of movement. During the typical shoulder joint dissection, we are unable to see the intracapsular view of shoulder joint. Methods: A dissection technique that was performed in Sharir Rachana Dept. of NIA, Jaipur, which exposes the glenohumeral joint’s internal capsule, the glenoid labrum, the proximal insertion of the long head of the biceps tendon, and the surfaces of the joint while protecting the posterior aspect of the capsule and the surrounding muscles and tendons that support the joint. Results: This new dissection method allowed the preservation of glenohumeral joint structures and provides a better understanding of its intracapsular view and related structures. Conclusion: The glenohumeral joint can be dissected using this new technique, by which we can prevent the damage to the structures that surround it and enabling visualization of its intracapsular view.